PROPOSING AND ANALYZING THE GENDER STEREOTYPE BEHAVIOR MODEL IN CHOOSING CHILDREN'S TOYS WITH SIMULATION DATA - Arundati Shinta (Jurnal Psikologi, 2006)
The gender stereotype behavior model in choosing children's toys consists of three latent variables i.e. the biological factor, cultural factor, and psychological characteristic. The later variable is endogen whilst the rests are exogenous and covariance. Each latent variable is converted by two observed variables i.e. the gender stereotype behavior and child rearing practice for describing the cultural influence; the testosterone hormone level and the preference in choosing partner based on race reason for describing the biological factor; aggressive behavior and spatial cognitive ability for describing psychological characteristic. Using the simulation data, the model is modified e.g. the spatial observed variable should be correlated with the gender stereotype observed variable. The modification model produces the significance level with the p = .171, the GFI is .990, and the RMSEAis .045. Those three crucial measurements have been appropriate to obtain the fit model. It is expected that the simulation data can explain the proposed model. Beside that it is proved that the biological factor is the covariance of the cultural influence (p < .05).